PREDICTING BINDING AFFINITIES OF FOSMIDOMYCIN ANALOGUES AS DOXP-REDUCTOISOMERASE INHIBITORS BASED ON STRUCTURE-CENTRIC APPROACHES - AMIYA KUMAR PATEL (International Journal of Pharma and Bio Sciences, 2012)
Fosmidomycin and its derivatives belong to class DOX-reductoisomerase (DXR) inhibitors. A fosmidomycin analogues library was designed with 43 analogues, their molecular interactions and binding affinities with DXR (PDB ID: 1ONP) have been studied using Glide docking, QM-polarized ligand docking (QPLD), molecular mechanics based on generalized Born/surface area (MM-GB/SA) and multi-ligand bimolecular association with energetics (eMBrAcE). Prediction models were developed between DXR inhibition activity (pIC50) of these compounds and molecular descriptors like Glide score, QPLDscore, binding energy and calculated free energy of binding. The r2 value ranges from 0.608-0.807 indicating good data fit, and r2cv ranges from 0.592-0.799 indicating acceptable predictive capabilities of models. Linear correlation between predicted and experimented pIC50 was observed (r2 = 0.603-0.781). Low root mean square error (0.39-0.84) of inhibitors was established in all structure-centric approaches, an efficient tool for generating potential and specific inhibitors of DXR by testing rationally designed lead compounds based on fosmidomycin derivatization.